Pengaruh Pemberian Reward dan Punishment Terhadap Keaktifan Belajar Siswa Kelas V di Sekolah Dasar - Nur Fitriya; Ismail Marzuki; Arissona Dia Indah Sari (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
The purpose of this study was to determine the effect of giving rewards and punishments on the learning activity of fifth grade students in elementary schools. This study used a quantitative approach with a pre-experimental design research type. The design used in this study was intact group comparison, this research design involved two classes with a total of 56 students. Among them are class V A as an experimental class, namely a class that was given the treatment of giving rewards and punishments during the learning process and class V B as a control class, namely a class that was not given the treatment of giving rewards and punishments during the learning process. The data collection technique in this study was using an observation sheet for student learning activity. While the data analysis technique used was a prerequisite test and a hypothesis test. The prerequisite test used in this study was a normality test and a homogeneity test with a significance level of α = 0.05. The results of the hypothesis proof using the T Test obtained a result of 0.000 with a significance level of α = 0.05, so it can be concluded that 0.000 > 0.05 so that H0 is rejected and H1 is accepted, which means that there is an influence of the use of rewards and punishments on the learning activity of fifth grade students at SD Negeri 28 Gresik.